In Vitro Effect of Alfa Mangostin on Multiresistant Uropathogenic Escherichia Coli - Rakhmawatie, Maya Dian; Rohmani, Afiana; Ahyar, Fariz Wafaul (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
Introduction: In Indonesia, the most commom uropatogen E. coli resistance has been to ampicillin (91.9%), ciprof loxacin (83.7%) and cefixime (67.6%). Î±-mangostin, a chemical compound, has been developed as a new antibiotics isolaated from herbal Garcinia mangostana L, but its effectiveness against multiresistant uropathogenic E. Coli has not been established.Objective: This study examined the effect of Î±-mangostin on growth of multiresistant E. coliMethods: Î±-mangostin Treatment of E. coli uropatogen bacteria was administered in vitro, using 14 levels of concentration 14; 28,13; 56.25; 112.5;225; And 450 Î¼g/mL with 4 times replication at each concentration. The antibacterial activity of Î±-mangostin was determined by evaluating bacterial growth at each concentration using the indirect method by sample absorbance reading. The Samples of uropatogen of E. coli treated with various doses of Î±-mangostin were incubated for 18-20 hours and then subjected to the absorbance reading using a UV-Vis spectrophotometer Î» 625 nm.Results: Minimum inhibitory concentration (MIC) in this study was 450 mg/mL. Based on linear regression (STATA 13.1) relationship betweenÎ±-mangostin concentrations and bacterial growth inhibition activity showed 0.0001 <0.05 showing that all concentrations of Î±-mangostin simultaneously had a significant effect on the growth of uropathogenic E. coli.Conclusion: Î±-mangostin has not been effective to inhibit the growth of multiresistent uropathogentic E. coli due to a relatively high MIC (450 mcg/mL).a Potentially relevant activity in the clinical setting will occur if the value of the MIC of a substance in vitro <100 Î¼g /mL. Even the pharmaceutical industry prefers the development of antibiotics with in vitro MIC value of â‰¤ 2 Î¼g/mL.